2022
DOI: 10.1097/psy.0000000000001099
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Function Is Associated With Multiple Indices of Adiposity in the Canadian Longitudinal Study on Aging: A Cross-Sectional Analysis

Abstract: ObjectivePrior studies have suggested reciprocal relationships between cognitive function and adiposity, but this has not been investigated with population representative data sets. The purpose of this study was to examine the association between cognitive function and adiposity in a large population-based sample of middle-aged and older adults. It was hypothesized that better scores on tests of cognitive function would be associated with lower adiposity, and this association would be primarily mediated throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Obesity is negatively associated with several indicators of cognitive function in adult populations; however, this relationship is less well studied in children and adolescents. A number of studies reported that excess adiposity in childhood is negatively associated with neurocognitive task performance .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity is negatively associated with several indicators of cognitive function in adult populations; however, this relationship is less well studied in children and adolescents. A number of studies reported that excess adiposity in childhood is negatively associated with neurocognitive task performance .…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Overweight children tend to remain overweight throughout their adulthood, and this excess adiposity substantially increases their risk of developing noncommunicable diseases, such as type 2 diabetes, heart diseases, and other chronic conditions at an early age. 2 Obesity is negatively associated with several indicators of cognitive function in adult populations [5][6][7][8] ; however, this relationship is less well studied in children and adolescents. A number of studies reported that excess adiposity in childhood is negatively associated with neurocognitive task performance.…”
Section: Introductionmentioning
confidence: 99%